DEVELOPMENT OF BALANCE INSTRUMENTS FOR CHILDREN 5-6 YEARS OLD - Pranoto, Nuridin Widya (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
Balance is one of the motor skills that is important to master from an early age. Having the ability to balance becomes a support for more complex movement abilities that are useful in carrying out movements in everyday life. This study aims to develop a balance instrument that can be used to measure the balance ability level of children aged 5-6 years. The method used in this research is research and development (R&D) using the ADDIE model with procedures (1) analysis (2) design (3) implementation (4) evaluation. A total of 30 children participated in this study with an age range of 4-6 years. Validity and reliability data were tested using SPSS 16. From the results of the study it was obtained (1) a complex balance test instrument for children with an age range of 5-6 years, (2) there were 30 balance test items which were declared valid, the value of r count > r table stating that this instrument is reliable and can be used as a balance measurement tool. Based on the results of the study, it can be concluded that the developed balance instrument can measure the components of balance in children aged 5-6 years.